Analisis Indikator Ekonomi Makro Di Negara-Negara ASEAN Terhadap Perangkap Negara Berpendapatan Menengah - Mifti Anisa Wulansari; I Wayan Suparta; Arivina Ratih (Jurnal Ekonomi Pembangunan, 2019)
This study observes how the opportunities of middle-income countries located in ASEAN avoid the Middle Income Trap. Human Development Index, Foreign Direct Investments, Goods and Services Exports, and the Government Effectiveness Index are regressed to GNI per capita with panel analysis. Secondary data are used and was published officially by the World Bank and the United Nations Development Program (UNDP) in 5 ASEAN Regional Countries, namely Indonesia, the Philippines, Malaysia, Thailand and Vietnam in the period 2004-2017. Also, this study discusses the contribution of the Incremental Capital Output Ratio (ICOR) coefficient to Gross Domestic Product. The results of the study state that there are significant and positive effects of the independent variables on the dependent variable. Expected that, it's essential to give priority to macroeconomics as a result of this research. For Advanced Research, you can use bonus demographic and investment variables to provide forecasting to avoid the Middle Income Trap.